The exploitation of limpets in a Mediterranean Marine Protected Area: assessing the effectiveness of protection in the intertidal zone - MARRA, STEFANO; COPPA, STEFANIA; CAMEDDA, ANDREA; MASSARO, GIORGIO; de LUCIA, GIUSEPPE A. (Mediterranean Marine Science, 2018)
Limpets are intertidal keystone grazers and their overexploitation could have significant consequences for intertidal communities. Limpets are harvested around the Sinis Peninsula (Sardinia, Italy) but harvesting is prohibited within the “Penisola del Sinis - Isola di Mal di Ventre” Marine Protected Area (MPA). This work assesses the effects of human harvesting on the population dynamics of three common Mediterranean species of Patella, namely, P. rustica, P. caerulea and P. ulyssiponensis, testing the effectiveness of the MPA and the role of site accessibility in limiting the intensity of such harvesting pressure. In the period between June 2015 and August 2016, limpet abundance and size were recorded on a monthly basis by means of photographic frames within linear transects at ten sites spread out along the coastline of the Sinis Peninsula to assess growth and temporal patterns. Limpets older than two years are extremely rare in the study area. Limpets are more abundant within the MPA in comparison with non-protected areas and within less accessible sites in comparison with areas where the intertidal zone is easily accessible from land. Despite this, overall human-induced mortality in the area is high, indeed the pool of limpets observed with a mean density of 104.3 ± 9.7 limpets/m2 during the first survey was reduced by 99.2%in less than one year. This work demonstrates that human harvesting strongly affects the population dynamics of Patella species in the area and that within the MPA this stressor is not efficiently reduced.